Does cooperative membership improve household welfare? Evidence from a panel data analysis of smallholder dairy farmers in Bihar, India. (February 2018) - Kumar, Anjani; Saroj, Sunil; Joshi, P.K.; Takeshima, Hiroyuki
Highlights: We examine the impact of dairy cooperatives on milk producers' farm performance. The study based on panel data uses endogenous switching regression model. Dairy cooperative has a positive impact on milk yield, profit, and food safety. Marginal farmers benefit more than small, medium, and large farmers.